Relationship between induced sputum eosinophils and the clinical pattern of childhood asthma. Issue 2 (1st February 2003) - Gibson, P G; Simpson, J L; Hankin, R; Powell, H; Henry, R L
Abstract : Background: The relationship between the clinical pattern of asthma and airway inflammation in childhood asthma is poorly characterised, yet underpins the treatment recommendations in current asthma guidelines. A study was undertaken to examine the relationship between airway inflammation and clinical asthma in children. Methods: Children with asthma (n=146) and healthy controls (C, n=37) were recruited from primary and specialist clinics. Sputum induction and hypertonic saline challenge were performed. Results: As the frequency of asthma episodes in the past 12 months increased, there were significant increases in sputum eosinophils (median; infrequent episodic (IE) 1.5%, frequent episodic (FE) 2.3%, persistent (P) 3.8%, control (C) 1.0%; p=0.002), sputum eosinophil cationic protein (ECP) (IE 113 ng/ml, FE 220, P 375, C 139; p=0.003), and desquamated bronchial epithelial cells (IE 2.0%, FE 6.0%, P 5.0%, C 2.5%; p=0.04). Treatment intensity was also associated with increased sputum eosinophils (p=0.005). The relationships between other severity markers (current symptoms, lung function) were less strong. Conclusion: Children with more frequent episodes of clinical asthma exhibit increasing airway inflammation that is characterised by sputum eosinophilia and bronchial epithelial desquamation. The results support clinical assessment by frequency of wheezing episodes over the past 12 months when determining anti-inflammatory treatment requirements, and indicate that current symptoms are determined by mechanisms in addition to sputum eosinophilia.